The Image of Hellenism and Greekness in Australian Literature at the End of the Second Millennium - Kanarakis, George (Études helléniques / Hellenic Studies, 1999)
The portrayal in Australian literature of Greeks and Greek culture is not a new phenomenon, although it is basically one of the post-World War II era. As we begin the new millennium it is appropriate to examine relevant works of current Australian literary writing to ascertain the form which this portrayal takes today. Leaving aside earlier writers and their works (however worthy), an investigation will be made into a wide range of recent works by contemporary Australian writers, while the varying depictions of Greeks and Greek culture will be located and examined. Particular attention will be paid to new approaches and mentalities which together illustrate a new development, and which in turn will be discussed within its socio-cultural context. After all, these externalized images and impressions which the body of Australian literature contains are the ones which this literature will carry with it into the next century, and which, to some extent, will influence the perceptions and possibly even the attitudes of its reading public.